2021
DOI: 10.21873/anticanres.15151
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Absolute Lymphocyte Count and Neutrophil-to-lymphocyte Ratio Are Prognostic Factors for Stage III Breast Cancer

Abstract: Background/Aim: Stage III breast cancer comprises a broad spectrum of disease, including the extent of supraclavicular/internal mammary lymph node metastasis. In this study, we evaluated the usefulness of the absolute lymphocyte count (ALC) and neutrophil-to-lymphocyte ratio (NLR) in predicting the prognosis of patients with stage III breast cancer. Patients and Methods: Seventy-five patients with stage III breast cancer who underwent surgery were included. We compared their clinicopathological factors accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…1,2 Local immune cell responses to breast tumors are well characterized and are associated with cancer progression and survival. [3][4][5][6][7] Peripheral blood leukocyte profiles measured after diagnosis may also be associated with prognosis, [8][9][10] but whether leukocyte subtypes are altered before diagnosis remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Local immune cell responses to breast tumors are well characterized and are associated with cancer progression and survival. [3][4][5][6][7] Peripheral blood leukocyte profiles measured after diagnosis may also be associated with prognosis, [8][9][10] but whether leukocyte subtypes are altered before diagnosis remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been established that immune cells play a fundamental role in controlling the initiation and progression of cancer 4 , 5 and that lymphocytes are the main source of adaptive antitumor immune responses. 4 In line with these findings, the peripheral absolute lymphocyte count (ALC) was reported to have an important prognostic role in many cancers, including gastric cancer, 6 pancreatic cancer, 7 breast cancer, 8 and CRC. 9 , 10 However, it is notable that ALC is limited due to its low efficacy in predicting the outcome of CRC.…”
Section: Introductionmentioning
confidence: 81%
“…NLR is an established prognostic predictor in various human cancers (9). For breast cancer, a systematic review conducted by Corbeau et al (10) revealed that the majority of studies showed negative prognostic correlation between all survival outcomes (DFS, BCSS and OS) and a high NLR (11)(12)(13), including in cohorts of patients receiving NAC (14,15). TIL is a predictor of response to NAC (16), and a robust prognostic factor for both treatment-naive and post-neoadjuvant chemotherapy breast cancers (17)(18)(19), and is recognized as an important histologic feature for breast cancer classi cation in the latest World Health Organization classi cation of tumours of the breast (20).…”
Section: Discussionmentioning
confidence: 99%